"Communicating Lily's Pain": A reflective narrative commentary about co‐creating a resource to provoke thinking and change about assessing and managing the pain of children with profound cognitive impairment. Issue 1 (7th February 2022) - Carter, Bernie; Young, Rob; Munro, James
Abstract: This paper draws together about 20 years of research work and discovery and the development of a resource about pain assessment and management in children with profound cognitive impairment. The animation tells the story of an imagined child called Lily and the skills her mother uses and the challenges that her mother faces in assessing and managing Lily's pain. The animation is built on stories drawn from qualitative research findings, conversations while in clinical practice and with members of the general public, parent advisers and other sources. Most of the "evidence" came from stories shared by parents and healthcare professionals. This paper draws on some elements of socio‐narratology and is predicated on the basis that stories are important and they can act on and with us. By using an animation to tell Lily's story, the intention was to communicate research findings to a wider and more diverse audience than the typical readership of an academic journal. The intention was to act in and on people's consciousness about children's pain and to strengthen relationships and create bonds between clinicians, parents, and children in pain to make their dialog more social, connected, and meaningful. All three of us—the researcher, the writer, and the animator—have been marked and "re‐shaped" by our work related to creating Lily; we have learned more about children like Lily and their mothers, and we have learned more about ourselves and our humanity. This animation is still a story in progress, a story 'in the wild', a story (and a resource) we would like you to re‐tell and share. The story of Lily's pain aimed to change the lives of parents and children and professionals. Our hope is that you can be part of that change. Abstract : This paper draws together more than 20 years of research work and discovery that led to the creation of an animation. The animation tells the story of an imagined child called Lily—a child with profound cognitive impairment who is unable to communicate about pain using usual methods. The animation shows the skills her mother uses, the challenges she faces in assessing and managing Lily's pain, and the importance of communication between parents and healthcare professionals.